Reuse of solid organic waste to produce biogas and compost as a circular economy process in an underground mining unit - (:unkn) unknown (LACCEI (Latin American and Caribbean Consortium of Engineering Institutions), 2024)
The main objective of the project is to carry out a cost-benefit analysis for the use of organic solid waste generated in a specific mining unit. Likewise, the main parameters that influence the treatment of organic waste to obtain biogas and compost are...
Keywords: Economía circular; Biogás